2007
DOI: 10.1111/j.1365-2109.2007.01841.x
|View full text |Cite
|
Sign up to set email alerts
|

Digestive enzyme activity of the red porgy (Pagrus pagrus, L.) during larval development under culture conditions

Abstract: The ontogenic development of the main digestive enzymes (proteases, amylase and lipase) in the red porgy, Pagrus pagrus, larvae was assayed during the larval development. The green water technique was carried out for larval rearing and whole-body homogenates were used for enzymatic assays in triplicate. Signi¢cant alterations in speci¢c activities of all digestive enzymes measured during the period of this study were mostly related to metamorphosis and weaning. Trypsin-and chymotrypsin-speci¢c activities were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 30 publications
9
39
2
1
Order By: Relevance
“…This is because the gut microflora in fishes and crustaceans can metabolize several nutrients that the host cannot and can convert them to end products that are beneficial to the host (Suzer et al, 2007;Hoyoux et al, 2009). It has been reported that intestinal microorganisms have a beneficial effect on the digestive process of fish such as in the microbial breakdown of cellulose (Saha and Ray, 1998;Bairagi et al, 2002;Saha et al, 2006;Mondal et al, 2008;Ray et al, 2010), starch (Sugita et al, 1997), protein (Chong et al, 2002;Fu et al, 2005;Silvia et al, 2006) and lipid (Tanu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the gut microflora in fishes and crustaceans can metabolize several nutrients that the host cannot and can convert them to end products that are beneficial to the host (Suzer et al, 2007;Hoyoux et al, 2009). It has been reported that intestinal microorganisms have a beneficial effect on the digestive process of fish such as in the microbial breakdown of cellulose (Saha and Ray, 1998;Bairagi et al, 2002;Saha et al, 2006;Mondal et al, 2008;Ray et al, 2010), starch (Sugita et al, 1997), protein (Chong et al, 2002;Fu et al, 2005;Silvia et al, 2006) and lipid (Tanu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, onset and changes of development patterns of trypsin and chymotrypsin in larval fish could be genetically controlled and increased by age and size . A similar pattern about activities of these protease increases in early stages and then relative reduction is reported in some Sparids such as P. erythrinus (Suzer et al, 2006), P. pagrus (Suzer et al, 2007b), sharpsnout seabream, Diplodus puntazzo (Suzer et al, 2007a) and other marine fish larvae such as herring larvae, Clupea harengus, (Pedersen and Andersen, 1992) and tilapia larvae, Oreochromis niloticus (Drossou et al, 2006). The above stated decline in specific enzyme activities of these digestive proteases during larval ontogeny of D. labrax could be basically explained by the normal increase of tissue proteins in growing larvae, which reflects anatomical and physiological changes in fish larvae, and does not correspond to a lowering in the amount of digestive enzymes or dietary shifts .…”
Section: Discussionmentioning
confidence: 53%
“…It was suggested that activity of some pancreatic enzymes, i.e., protease, amylase could be defined related with morphological development of zymogen granules according to other authors (Caruso et al, 2001;Micale et al, 2006;Suzer et al, 2007c). Additionally, it is reported that ontogenetic expression digestive proteolytic enzymes, trypsin and chymotrypsin, and also amylase were detected concurrently with the formation of zymogen granules in some cultured species such as common pandora, Pagellus erythrinus (Suzer et al, 2006), red porgy, Pagrus pagrus (Suzer et al, 2007b), Senegale sole, Solea senegalensis (Ribeiro et al, 1999), and yellowtail kingfish, Seriola lalandi (Chen et al, 2006). Furthermore, as in some Sparid larvae, the cells of the liver and pancreas of D. labrax are similar to each other and liver appeared compact basophilic tissue next to the yolk-sac (Sarasquete et al, 1995;Guyot et al, 1995;Santamaria et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This species contributes significantly to commercial fishing in Argentina (Cotrina, 1989;Cotrina & Raimondo, 1997) and is considered of great potential for aquaculture diversification (Pajuelo & Lorenzo, 1996;Maragoudaki et al, 1999;Suzer et al, 2007;Schuchardt et al, 2008). Even though several studies on development of red porgy have been carried out, as far as we know, there are no previous studies on larval condition of this species.…”
Section: Introductionmentioning
confidence: 92%